A digital time skew calibration technique for time-interleaved ADCs - Qiu, Lei (2016)
In this paper, a digital time skew calibration technique for time-interleaved (TI) ADCs is presented. The time skew calibration for TI-ADCs in analog domain suffers from limited correction accuracy and additional jitter. And the proposed digital time skew calibration method estimates the polarity of the time skew through correlation of adjacent channels and corrects the time error by adopting adaptive fractional delay filters iteratively. Simulation results show that, in a 4-channel 1GS/s 12-bit TI-ADC system, the SFDR can be improved to 78dB by 5-order FIR filters within a calibration range of [-0.005/fs, +0.005/fs].